197k views
2 votes
What is the solution to this using substitution method pls show ur work

What is the solution to this using substitution method pls show ur work-example-1
User JackoM
by
5.5k points

1 Answer

6 votes

Answer:

x=-6, y=0

Explanation:

Use the 3x-9y=-18 equation and add 9y to both sides to have 3x on its own on the left side. Then, divide by 3 on both sides. Then you'll have x=-6+3y. Plus this back into the 5x+4y=-30 equation and you'll get 5(-6+3y)+4y=-30. Use the distributive property and you'll get -30+15y+4y=-30. Simplify and get -30+19y=-30, then add 30 to both sides and you'll get 19y=0. Divide by 19 on both sides and you'll get y=0. Now that we know y=0, plug that back into the 5x+4y=-30 equation, and you'll get 5x+4(0)=-30. Simplify and you'll get 5x=-30. Divide by 5 on both sides and you'll get x=-6.

User Drstevens
by
5.6k points